The Relationship Between the Leadership Style of the Head of the room and the Motivation of Nurses to Work in the Nurse's room at RSIA Cicik Hospital - Hamdani; Ilda Melisa (CV. Get Press Indonesia, 2024)
Nursing is a profession that is of great importance in the context of health services provided in hospitals. The quality of health services is significantly influenced by the performance of nurses who work in various treatment rooms. The objective of this study is to identify and analyse the relationship between the leadership style of the head of the room and the nurses’ desire to work in the nurses’ room of the RSIA Cicik Hospital. This study employed a quantitative research design with a descriptive cross-sectional study approach. 25% of employees had high motivation, while 75% had low motivation according to the authoritarian perspective. On the democratic side, 85.7% of employees had high motivation. With a p-value of 0.02, this relationship showed statistical significance. According to the democratic analysis, 30% of staff members have low motivation and 70% have high motivation. According to the authoritarian analysis, 87.5% of staff members have low motivation. As evidence of the statistical significance of this relationship, the p-value is 0.025. In the democratic perspective, 18.2% of staff members had low motivation and 81.8% had high motivation, while the authoritarian perspective showed that 75% of staff members had low motivation. This relationship has statistical significance with a p-value of 0.07. It would be beneficial for hospital management and ward heads to consider adopting a more democratic leadership style. To this end, ward leaders may benefit from undertaking leadership training, which will equip them with the skills required to manage teams in a more inclusive and supportive manner.